A Survey of Ectoparasite occurrences on birds from two contrasting habitats in Kuchibg Division, Sarawak. - Ainur Nasrin, Binti Mahadi (Universiti Malaysia Sarawak (UNIMAS), 2017)
A study of ectoparasites on birds was done at two contrasting habitats in Kuching Division, Sarawak. Two surveys was conducted from 23 to 26 September 2016 at Dered Krian National Park (DKNP), Bau and from 25 to 28 October 2016 at Kampung Stunggang Melayu Barn (KSMB) in Lundu. A total of 59 individuals of 28 bird species belonging to 17 families were caught and examined for ectoparasite infestation. Of these birds, three families of mites (Trouessartiidae, Alloptidae and Pterolichidae) and three families of lice (philopteridae, Menoponidae and Ricinidae) were collected. Most lice were known to be host-specific while mites tend to shift from one bird to one another through body contact. KSMB have the highest ectoparasites diversity compared to DKNP. All 11 species ofbirds (39.29%) were infested by at least one ectoparasite species. A total of 253 individuals of ectoparasites comprised of 12 species from 11 genera. The infestation rates were 100% for Apodiformes and Columbiformes, 63.64% for Charadriiformes, 50% for Coraciiformes and 15.39% for Passeriformes. Astigmatid mite occurrence was common on forest birds and paddy field bird while Mallophaga (chewing lice) was found dominated on family Columbidae.